The reliability of the standard deviation bid method for awarding construction contracts - Sudarshan Tiwari; Madhav Prasad Koirala; Santosh Kumar Shrestha; Om Prakash Giri (Advances in Engineering and Technology: An International Journal, 2023)
This study examines the complex test of observing to time, cost, and quality factors when executing construction projects in developing countries, which frequently becomes more difficult by awarding projects based on low bids. By compared to collusion implications and e-bidding benefits using the standard deviation bid and average bid methods, the study provides light on critical aspects. An examination of contracts in Nepal’s Gandaki province between 2018 and 2022 yields interesting results. When there is no collusion, both bidding methods produce similar results. The average bid method, on the other hand, is subject to collusion, whereas the standard deviation bid method is not. To address the constraints associated with low bids, a cautious recommendation for the average bid method is made, along with vigilance against collusion. The standard deviation bid method, on the other hand, emerges as an effective obstacle to collusive behavior. To enhance the bid procedures, the study encourages for additional qualification criteria such as financial weighting and enhanced performance bonds. These amendments to Nepal’s Public Procurement Act (PPA) and Public Procurement Regulation (PPR) of 2007 are intended to address issues raised by low bids. The importance of e-bidding practices is highlighted for digital transformation and corruption prevention. The study emphasizes the importance of putting in place mechanisms to detect collusion across bid selection methods. The research concludes with an invitation for experimental exploration of the Standard Deviation Bidding Method (SDBM), with an evaluation of its efficiency across time, cost, and quality domains. This investigation has the potential to reveal the best bid selection methodology for construction projects.